Youth labour markets in Europe and Central Asia - Niall O'Higgins (Institute for the Study of Labor (IZA), 2010)
Transition to the market economy in ECA opened up a range of potential opportunities for young people. It has also raised a series of challenges. Youth unemployment and joblessness have emerged as serious problems with the potentially very high costs. Formal Education and Training systems have been slow to adapt to the changing requirements placed upon them by the rapidly changing industrial structure arising from transition. The damage arising from on the one hand rising expectations and on the other the failure of systems to accommodate these is likely to have long-term consequences. It is important then that countries in ECA support young people in fulfilling their potential. This paper looks at developments in and around the transition of young people from education to work in the ECA region in recent years. The purpose of the paper is to aid understanding of the current situation and to suggest areas where action is most needed and is likely to be most effective. The first section considers developments in the general economic context of relevance to young people. Section 2 goes onto consider the current situation of (and trends in) factors affecting young people's entry into work. Section 3 assesses policies affecting youth employment and unemployment and section concludes identifying key issues and areas where action is needed and where it is likely to be effective.
urn:nbn:de:101:1-201008116885
Keywords: I28; J08; J13; J24; 330; youth labour markets; Europe and Central Asia; active labour market policies; vocational education and training; joblessness